2018
DOI: 10.1002/hpm.2535
|View full text |Cite
|
Sign up to set email alerts
|

Have out‐of‐pocket health care payments risen under free health care policy? The case ofSriLanka

Abstract: SummaryCompared to its neighbors, Sri Lanka performs well in terms of health. Health care is provided for free in the public sector, yet households' out‐of‐pocket health expenditures are steadily increasing. We explore whether this increase can be explained by supply shortages and insufficient public health care financing or whether it is rather the result of an income‐induced demand for supplementary and higher quality services from the private sector. We focus on total health care expenditures and health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Because of the limited scope and high cost of private sector facilities, government hospitals, clinics and other peripheral services must cater to a larger proportion of the healthcare demand coming from general public (World Bank, 2013). The resource constraints faced by the government sector result in it facing numerous issues such as shortage of medicines, limited access to specialist treatment and inconsistent service standards (Pallegedara and Grimm, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the limited scope and high cost of private sector facilities, government hospitals, clinics and other peripheral services must cater to a larger proportion of the healthcare demand coming from general public (World Bank, 2013). The resource constraints faced by the government sector result in it facing numerous issues such as shortage of medicines, limited access to specialist treatment and inconsistent service standards (Pallegedara and Grimm, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Findings revealed that medical poverty is high among chronic NCDs. In another study, Pallegedara and Grimm [ 43 ] stressed that older persons are more inclined to suffer from chronic diseases. The two-part model based on the 2012/2013 household survey was carried out to examine the association of NCD-prevalence and healthcare utilization with household consumption [ 44 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Sri Lanka, Pallegedara [ 16 ] examined the effects of chronic NCDs on household’s out-of-pocket health expenditures and found that medical poverty is high among chronic NCDs. Pallegedara and Grimm [ 17 ] further highlight that older persons are more likely to suffer from chronic diseases. In order to examine the association of NCD-prevalence and healthcare utilization with household consumption, Kumara and Samaratunge [ 18 ] employed the two-part model using the 2012/2013 household survey and found private healthcare utilization was negatively related with household consumption.…”
Section: Literature Reviewmentioning
confidence: 99%